Functional Hemispheric (A)symmetries in the Aged Brain—Relevance for Working Memory - Esteves, Madalena; Magalhães, Ricardo; Marques, Paulo; Castanho, Teresa C.; Portugal-Nunes, Carlos; Soares, José M.; Almeida, Armando; Santos, Nadine C.; Sousa, Nuno; Leite-Almeida, Hugo (Frontiers in Aging Neuroscience, 2018)
Functional hemispheric asymmetries have been described in different cognitive processes, such as decision-making and motivation. Variations in the pattern of left/right activity have been associated with normal brain functioning, and with neuropsychiatric diseases. Such asymmetries in brain activity evolve throughout life and are thought to decrease with aging, but clear associations with cognitive function have never been established. Herein, we assessed functional laterality during a working memory task (N-Back) in a healthy aging cohort (over 50 years old) and associated these asymmetries with performance in the test. Activity of lobule VI of the cerebellar hemisphere and angular gyrus was found to be lateralized to the right hemisphere, while the precentral gyrus presented left>right activation during this task. Interestingly, 1-Back accuracy was positively correlated with left>right superior parietal lobule activation, which was mostly due to the influence of the left hemisphere. In conclusion, although regions were mostly symmetrically activated during the N-Back task, performance in working memory in aged individuals seems to benefit from lateralized involvement of the superior parietal lobule.